Trends and Innovation in Digital Reading Assessment: A Decade of Bibliometric Insights - Saputra, Wendi; Cahyani, Isah; Sastromiharjo, Andoyo (JOLLT Journal of Languages and Language Teaching, 2025)
The digitalization of reading assessment has become inevitable. The emergence of technology in reading assessment should be seen as an opportunity to improve the quality of students’ reading. This study aims to compile various research conducted on digital reading assessment. The method used in this research is a literature review, where the researcher gathers information through literature studies including books, articles, research findings, and others. The researcher then analyzes the collected data using bibliometric analysis. Bibliometric analysis is an approach that employs a range of quantitative methods to measure, analyze, and track scientific literature. The results of this research found 29 articles related to digital-based reading assessment from 2013 to 2023. After analysis, several topics were frequently discussed in these articles, including assessment, computer-based assessment, technology, online testing, and open book. However, there are still some topics that need further development, such as computation design, reading comprehension assessment, cooperative/collaborative learning, and active reading. This research will be highly beneficial for researchers looking to develop digital reading assessments, ensuring that this form of assessment advances in the future and produces the best digital-based reading evaluations.